Revisionary notes on the genera Symplanella Fennah, 1987 and Pseudosymplanella Che, Zhang et Webb, 2009 (Hemiptera: Fulgoromorpha: Caliscelidae, Ommatidiotinae), with description of new subgenera and new species - Gnezdilov, Vladimir M. (Zootaxa, 2024)
The genus Symplanella Fennah, 1987 is revised, with the type species, Symplanella breviceps Fennah, 1987, is redescribed and illustrated based on new material from Thailand. A new subgenus, Bambunella subgen. nov. (type species: Symplanella zhongtua Yang et Chen, 2014), is erected in the genus Symplanella. A new species, Symplanella (Bambunella) cattiensis sp. nov., is described from southern Vietnam. The genus Pseudosymplanella Che, Zhang et Webb, 2009 is revised, with a new subgenus, Nelobamba subgen. nov. (type species: Pseudosymplanella maxima Gong, Chen et Yang, 2023), is erected. A new species, Pseudosymplanella (Nelobamba) kubani sp. nov., is described from northern Laos. Key to the subgenera and species of the genera Symplanella and Pseudosymplanella are given. Male sternal apodemes and abdominal sternites IV–VI in Augilini are briefly discussed.